Rapidly In Situ Forming Platelet-Rich Plasma Gel Enhances Angiogenic Responses and Augments Early Wound Healing after Open Abdomen - Bo Zhou; Jianan Ren; Chao Ding; Yin Wu; Dong Hu; Guosheng Gu; Jieshou Li (Gastroenterology Research and Practice)
Objective. The purposes of our present study were to evaluate the potential of platelet-rich plasma gel to enhance granulation tissue formation after open abdomen and to examine whether the effect was attributable to stimulating rapid neovascularization. Methods. Twenty-four rats underwent colon ascendens stent peritonitis surgery to induce sepsis, followed by intraperitoneal injection of nitrogen to create intra-abdominal hypertension. Four hours later, laparotomies were performed. The rats were randomized into three groups (n=8 for each group): control, platelet-poor plasma (PPP), and platelet-rich plasma (PRP) groups. One week after the treatment, granulation tissue formation and angiogenesis were evaluated by histological and laser Doppler analysis. Results. The resultant platelet count in platelet-rich plasma was higher than that of PPP. The concentrations of platelet-derived growth factor BB, transforming growth factor β-1, and vascular endothelial growth factor in PRP were significantly higher when compared with that of PPP. Myofibroblast count, granulation tissue thickness, vessel numbers, and blood perfusion were increased in PRP group, followed by PPP group, with control being the least. Conclusion. Rapidly in situ forming platelet-rich plasma gel promoted remarkable neovascularization and early wound healing after open abdomen and may lead to novel and effective treatments for open abdominal wounds.